2014
DOI: 10.1016/j.ssc.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Significant enhancement of superconductivity under Hydrostatic pressure in CeO0.5F0.5BiS2 superconductor

Abstract: We report the effect of hydrostatic pressure (0 -1.97 GPa) on the superconductivity of

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…In this study, we have revealed that the tetragonal structure does not change with Se substitution up to x = 0.7. On the basis of these facts, we assume that the partial substitution of S by Se could enhance superconductivity, but it could not induce the higher-T c phase as those revealed in previous high-pressure studies of BiS 2 -based superconductors [21,22,26,27]. …”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…In this study, we have revealed that the tetragonal structure does not change with Se substitution up to x = 0.7. On the basis of these facts, we assume that the partial substitution of S by Se could enhance superconductivity, but it could not induce the higher-T c phase as those revealed in previous high-pressure studies of BiS 2 -based superconductors [21,22,26,27]. …”
Section: Introductionmentioning
confidence: 59%
“…Namely, element substitution at the blocking layer is effective for inducing superconductivity and tuning its superconducting properties in BiS 2 -based superconductors. Furthermore, several high-pressure studies revealed that superconducting properties are sensitive to changes in local crystal structures: the T c can be enhanced by optimal lattice contraction [20][21][22][23][24][25][26][27]. In addition, it was reported that the [31].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Sr 0.5 La 0.5 FBiS 2 polycrystalline sample, the semiconductor-metal transition was considered as coming from the change of F-Sr/La-F bond angle along with inter-atomic distances [25]. Interestingly, the semiconductor-metal transition under pressure for CeO 0.5 F 0.5 BiS 2 system has been proposed according to the first-principle calculations [33], but the transition was not observed in previous reports of experiment [23,26]. In particular, for LaO 0.5 F 0.5 BiS 2 polycrystalline samples, the normal state resistivity decreases monotonically with increasing pressure, but it still exhibits semiconducting behavior under a very high pressure (18 GPa) [27].…”
mentioning
confidence: 99%
“…In this * Electronic address: zhuxiyu@nju.edu.cn, hhwen@nju.edu.cn newly found BiS 2 family, high pressure has been recognized as an important tool to enhance both the superconductivity volume and transition temperatures except for Bi 4 O 4 S 3 [22][23][24][25][26][27][28]. In particular, the SC transition temperature of REO 1−x F x BiS 2 (RE=La, Ce, Nd, Pr) [22][23][24] and Sr 1−x RE x FBiS 2 (RE = La, Ce, Nd, Pr, Sm) [25,28] systems was enhanced tremendously by applying the hydrostatic pressure.…”
mentioning
confidence: 99%
“…The highest T c =10.6 K has been obtained for LaO 0.5 F 0.5 BiS 2 superconductors under hydrostatic pressure [11]. In particular, the T c of REO 1−x F x BiS 2 (RE=La, Ce, Nd, Pr) [11][12][13][14] and Sr 1−x RE x FBiS 2 (RE = La, Ce, Nd, Pr, Sm) systems, enhances tremendously by applying the hydrostatic pressure [15,16]. As far as the chemical substitutions are concerned the doping of Se on the S site in the Bi 4 O 4 S 3-x Se x and NdOFBiS 2-x Se x superconductors showed the suppression in T c [17,18].…”
mentioning
confidence: 99%